ニホン ナンキョク チイキ カンソクタイ ニ オケル エットウ キカン チュウ ノ シガイセン ショウガイ シッカン ノ ブンセキ ナンキョク ニ オケル シガイセン ショウガイ ノ セイイン ノ トクチョウ ト シッカン ハッセイ ノ キセツ テキ オヨビ ネンジ テキ ヘンカ ノ ケントウ - 大野, 義一郎; オオノ, ギイチロウ; 宮田, 敬博; ミヤタ, タカヒロ; Ohno, Giichiro; Miyata, Takahiro (2000)
P(論文) JARE越冬隊における紫外線障害疾患について調査した。39次隊で発生した傷病総数199件のうち本疾患は8件(4%)で日光皮膚炎, 雪目, 口唇炎, 口角ヘルペスなどである。これらはすべて顔面周囲に限局していた。作業中の顔面への紫外線照射量を調べるため, 水平方向の紫外線量を測定した。夏の南極では, 太陽高度角が低いことと雪面反射により水平方向の紫外線量は赤道近辺に匹敵し, オゾンホール出現中の11月には赤道近辺以上となった。また日照時間と屋外作業時間が長くなることは被爆総線量をさらに増やす。これらは夏の南極における本疾患発生の特徴である。JARE歴代傷病総数4233件のうち紫外線関連疾患は127件(3.2%)であった。季節別では冬の極夜期はほとんどなく春夏秋に発生し11月が最多であった。経年変化では1990年代より増加傾向を示した。この増加は春期の発生が増加したことによる。これはオゾンホールの出現・増大年代, 出現季節と一致していた。 The incidences of diseases due to UV radiation in wintering personnel of the Japanese Antarctic Research Expedition (JARE) were studied. Medical consultations of JARE-39 included 199 cases. 8 of which were due to UV radiation; photo dermatitis, dermatitis, angular cheilosis, cheilosis and UV ophthalmia, all of which were observed near the face. The intensity of UVB radiation from the horizontal direction was measured. It was found that low solar elevation angle and high snow surface reflection enhanced UV radiation in the horizontal direction during the Antarctic summer to equal or more than that observed in the equatorial zone. Prolonged daytime and outdoor work in the Antarctic summer increases exposure to UV radiation. causing diseases due to UV in the Antarctic summer. Of 4233 clinical cases of JARE between 1956 to 1999,the number of UV related diseases was 127 (3.2%). The diseases were observed in spring, summer and autumn with a maximum in spring and no cases in winter. The diseases have been increasing since the 1990s, when the ozone hole was observed. Furthermore the diseases are observed mainly in spring when the ozone hole is in its maximum phase. departmental bulletin paper